Direct Gingival Fibroblast/Osteoblast Transdifferentiation via Epigenetics. (May 2017) - Cho, Y.; Kim, B.; Bae, H.; Kim, W.; Baek, J.; Woo, K.; Lee, G.; Seol, Y.; Lee, Y.; Ku, Y.; Rhyu, I.; Ryoo, H.
Alveolar bone resorption caused by trauma or periodontal diseases has represented a challenge for both dental clinicians and researchers. In this study, we evaluate the osteogenic potential of human gingival fibroblasts (HGFs) through a direct transdifferentiation from HGFs to functional osteoblasts via epigenetic modification and osteogenic signaling with bone morphogenetic protein 2 (BMP2) in vitro and in vivo. HGF treatment with 5-aza-2′-deoxycytidine (5-aza-dC) induced demethylation in the hypermethylated CpG islands of the osteogenic lineage marker genes RUNX2 and ALP, and subsequent BMP2 treatment successfully drove the fibroblasts to the osteoblasts' lineage. Cell morphological changes viewed under microscopy and alkaline phosphatase (ALP) and alizarin red S (ARS) staining confirmed the osteoblastic change mediated by epigenetic modification as did real-time polymerase chain reaction (PCR), methylation-specific PCR (MSP), and chromatin immunoprecipitation (ChIP) assay, which demonstrated the altered methylation patterns in the RUNX2 and ALP promoter regions and their effect on gene expression. Furthermore, micro–computed tomography (CT) analysis of in vivo mouse cell transplantation experiments showed high-density signal in the epigenetically modified HGF group; in addition, a significant amount of bone formation was observed in the transplanted material using hematoxylin and eosin (H&E) staining as well. Collectively, our results indicate that epigenetic modification permits the direct programming of HGFs into functional osteoblasts, suggesting that this approach might open a novel therapeutic avenue in alveolar bone regeneration.